Electron heating and thermal relaxation of gold nanorods revealed by two-dimensional electronic spectroscopy - Aude Lietard (Nature Portfolio, 2018)
Electron dynamics in plasmonic nanoparticles are often studied with transient absorption spectroscopy. Here, Lietard et al. apply two-dimensional electronic spectroscopy, a method generally used for molecular spectroscopy, to study ultrafast nonlinear dynamics of electrons in excited gold nanorods.